Supercapacitor Module Sizing concerning Operational Constraints of the Power Converter - Frivaldsky, Michal; Biel, Zdeno; Pcola, Marcel; Kacsor, Gabriel; Franko, Marek; Surovy, Juraj (Communications - Scientific Letters of the University of Zilina, 2023)
In this paper, the focus is given on the potential use of the supercapacitor component for peak power delivery, required during operation. Potential application use considered here is electric drive for robotic arm motorization. Automatization of industrial and manufacturing processes requires increasing demands on the use of industrial robots. The motion profiles of such system, requires within the operation peak power demand. The supply system can be composed from DC bus power supply, or combined with energy storage system. Combination with proper energy storage component, can improve energy efficiency and provide peak power for the requirements of the system operation. In this paper, design approach for supercapacitor (SC) module is presented for certain motion profile, which is defined by power requirement here. SC module design reflects input to output electrical specifications, while the most optimal configuration is being identified according to SC operation. This approach refers also to the identification of the operational performance of DC-DC bidirectional converter and its proper topological configuration.
Keywords: energy storage; supercapacitor; module; bidirectional converter